Serum Anti-Thyroglobulin Autoantibodies Are Specific in Predicting the Presence of Papillary-like Nuclear Features and Lymphocytic Infiltrate in the Thyroid Gland - Daniela Cabibi; Antonino Giulio Giannone; Sandro Bellavia; Roberta Lo Coco; Anna Lo Bianco; Eleonora Formisano; Gregorio Scerrino; Giuseppa Graceffa (Diagnostics, 2023)
(1) Background: Previous studies have reported a correlation between serum anti-Thyroglobulin-antibodies (TgAb) and papillary thyroid carcinoma. The aim of our study was to evaluate whether serum TgAb and anti-thyroid-peroxidase antibody (TPO) positivity was also related to pre-neoplastic histological changes such as papillary-like nuclear features (PLNF) and with the presence of lymphocytic infiltrate (LI) in thyroid surgical specimens. (2) Methods: The study was retrospectively carried out on 70 consecutively recruited patients who underwent thyroidectomy for benign process and whose TgAb and TPOAb values were retrieved from clinical records. Histological sections of thyroid surgical samples were revised, looking for PLNF and lymphocytic infiltrate. HBME1 expression was assessed by immunohistochemistry. (3) Results: Our results showed a significant association between TgAb, PLNF, and lymphocytic infiltrate. The presence of TgAb was highly specific, but less sensitive, in predicting the presence of PLNF (sensitivity = 0.6, specificity = 0.9; positive predictive value (PPV) = 0.88; negative predictive value (NPV) = 0.63). TgAb positivity showed a good association with the presence of lymphocytic infiltrate (sensitivity = 0.62, specificity = 0.9; PPV = 0.88 and NPV = 0.68). HBME1 immunoreactivity was observed in the colloid of follicles showing PLNF and/or closely associated with LI. (4) Conclusions: The presence of PLNF and LI is associated with serum TgAb positivity. The presence of TgAb and of LI could be triggered by an altered thyroglobulin contained in the HBME1-positive colloid, and could be a first defense mechanism against PLNF that probably represent early dysplastic changes in thyrocytes.